2000
DOI: 10.1007/s00585-000-1154-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmospheric oscillations on the field-aligned ion motions in the polar F-region

Abstract: Abstract. The ®eld-aligned neutral oscillations in the F-region (altitudes between 165 and 275 km) were compared using data obtained simultaneously with two independent instruments: the European Incoherent Scatter (EISCAT) UHF radar and a scanning FabryPerot interferometer (FPI). During the night of February 8, 1997, simultaneous observations with these instruments were conducted at Troms , Norway. Theoretically, the ®eld-aligned neutral wind velocity can be obtained from the ®eld-aligned ion velocity and by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In the recovery phase, modeling studies using the National Center for Atmospheric Research Thermosphere Ionosphere General Circulation Model (NCAR‐TIGCM) have found that the neutrals are capable of driving the westward trueE×trueB ionospheric drifts for 5–6 h after the magnetospheric convection declines [ Deng et al , ; Lyons et al , ]. On the observational side, Oyama et al [] used ISR and Fabry‐Perot interferometer (FPI) observations at high latitudes to determine that neutrals drive field‐aligned ion oscillations on a time scale of ∼40 min. Most of these previous works relied heavily on thermospheric models and/or colocated coverage of ISR and FPI instruments at high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In the recovery phase, modeling studies using the National Center for Atmospheric Research Thermosphere Ionosphere General Circulation Model (NCAR‐TIGCM) have found that the neutrals are capable of driving the westward trueE×trueB ionospheric drifts for 5–6 h after the magnetospheric convection declines [ Deng et al , ; Lyons et al , ]. On the observational side, Oyama et al [] used ISR and Fabry‐Perot interferometer (FPI) observations at high latitudes to determine that neutrals drive field‐aligned ion oscillations on a time scale of ∼40 min. Most of these previous works relied heavily on thermospheric models and/or colocated coverage of ISR and FPI instruments at high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The time constant for momentum transfer from neutral particles to ions is considerably shorter than the EISCAT radar time resolution that is normally longer than a few tens of seconds. This means that neutral wind drag causes observed FA ion oscillations in phase with thermospheric wind variations for oscillate at periods longer than the time constant for neutral‐ion collision effects [ Oyama et al , 2000]. The magnitude of FA ion diffusion velocity caused by plasma pressure gradients and gravity becomes comparable or larger than effects from FA neutral wind drag with increasing height above the F2 peak [ Lilensten and Lathuillere , 1995].…”
Section: Introductionmentioning
confidence: 99%